Changes in the gut microbiota structure and function in rats with doxorubicin-induced heart failure - Fan, Yawen; Liang, Lichang; Tang, Xinzheng; Zhu, Jinxian; Mu, Lei; Wang, Mengni; Huang, Xuecheng; Gong, Shenglan; Xu, Jinghan; Liu, Tianjiao; Zhang, Tianfeng (Frontiers in Cellular and Infection Microbiology, 2023)
The rat model of heart failure (HF) induced by doxorubicin (DOX), a broad spectrum and highly effective chemotherapeutic anthracycline with high affinity to myocardial tissue that causes severe dose-dependent irreversible cardiotoxicity, has been widely recognized and applied in studies of HF pathogenesis and drug therapy. The gut microbiota (GM) has attracted great attention due to its potential role in HF, and research in this area may provide beneficial therapeutic strategies for HF. Considering the differences in the route, mode and total cumulative dose of DOX administration used to establish HF models, the optimal scheme for studying the correlation between the GM and HF pathogenesis remains unclear. Therefore, with a focus on establishing the optimal scheme, we evaluated the correlation between GM composition/function and DOX-induced cardiotoxicity (DIC). Three schemes were investigated: DOX (at total cumulative doses of 12, 15 or 18 mg/kg using a fixed or alternating dose via tail vein or intraperitoneal injection) was administered to Sprague Dawley (SD) for 6 consecutive weeks. The M-mode echocardiograms performed cardiac function evaluation. Pathological changes in the intestine were observed by H&E staining and in the heart by Masson staining. The serum levels of N-terminal pre-B-type natriuretic peptide (NT-proBNP) and cardiac troponin I (cTnI) were measured by ELISA. The GM was analysed by 16S rRNA gene sequencing. Strikingly, based on the severity of cardiac dysfunction, there were marked differences in the abundance and grouping of GM under different schemes. The HF model established by tail vein injection of DOX (18 mg/kg, alternating doses) was more stable; moreover, the degree of myocardial injury and microbial composition were more consistent with the clinical manifestations of HF.